Study of cardiac markers in suspected myocardial infarction patients. - Mahato, Arun Kumar (2010)
ABSTRACT: Introduction: Cardiac markers are the substance that is released in to blood stream in myocardial infarction which is disease in which death of muscle occurs due to ischemia. Objectives: Aim of the study was to find prevalence of myocardial infarction and to differentiate between late and early diagnosis. Material and methods: The study population comprised 113 suspected cases among 2861 patients visiting Emergency Laboratory of Tribhuvan University Teaching Hospital from 11th October to 9th December 2009. Serum levels of different cardiac markers used were determined spectrophotometrically. The data were analyzed using statistical package for social sciences SPSS 14. Results: Among the suspected cases (N=113, M=57, F=56, Age=8-92 years), 22(19.46%) were found to have myocardial infarction (% of CK-MB >6) which include 8(14.03%) male and 14(25%) female. Prevalence of myocardial infarction was higher in the age group above fourty. 26(23%) patients were among the late presenters of myocardial infarction. Conclusion: According to the present finding, prevalence of myocardial infarction among the suspected cases was found to be 19.46% which was higher in age group above 40 consisting higher prevalence in female population i.e.12.38% with 23% of patients were among the late presenters of myocardial infarction. Keywords: Creatine kinase, Aspartate amino transferase, Lactate dehydrogenase, Myocardial infarction